Anxiety First Aid Effective to Reduce Adolescent’ Anxiety - Febriana Sartika Sari; Irna Kartina; Intan Maharani Sulistyawati Batubara; Mariyati Mariyati (GLOBAL HEALTH SCIENCE GROUP, 2020)
Adolescents go through a transitional period with many changes both physiological and psychological. The changes that occur in adolescents cause anxiety in adolescents. Prolonged anxiety can lead to panic attacks and anxiety disorder. These problems greatly interfere with the mental development of adolescents and reduce youth productivity and achievement. One of the attempts to reduce anxiety is giving Anxiety First Aid (AFA), which is a series of help to deal with anxiety. The study aimed to identify the effect of Anxiety First Aid to anxiety score. Method: The study used quasi-experimental design which involved pre-posttest with control group. The study was conducted in Senior High School Al Islam 1 Surakarta on July-September 2020. The population was senior high school students in Senior High School Al Islam 1 Surakarta. Samples were selected with purposive sampling technique that met the inclusion criteria. Subjects were 60 respondents consisting of 30 in each group obtained by a simple random sampling technique. The measurement of anxiety in the adolescents was by using Taylor Manifest Anxiety Scale. An independent t-test performed the analysis. The result of the research showed that anxiety score decreased significantly in those two groups. In contrast, the treatment group’s decrease in anxiety indicates a higher decrease than the control group. Anxiety First Aid (AFA) is recommended to decrease anxiety in adolescent especially in senior high school students.